Socio-Technical Analysis of Trust and Adoption in Blockchain Platforms (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Blockchain platforms promise trustless interaction -- transactions validated by mathematics rather than institutions. Yet adoption remains stubbornly low outside speculative trading: fewer than 5% of internet users have interacted with a blockchain application for non-speculative purposes, and enterprise blockchain deployments have a 70% failure rate within three years. The gap between technical capability and real-world adoption is not primarily technical -- it is socio-technical. Users must trust the user interface, the wallet software, the smart contract code, the protocol governance, and the broader ecosystem before they trust the cryptographic guarantees. Enterprises must trust the technology, the vendor ecosystem, the regulatory trajectory, and the interoperability roadmap. We present the Socio-Technical Trust and Adoption Framework (STTAF), combining quantitative on-chain adoption metrics with qualitative survey data from 1,240 individual users and 186 enterprise decision-makers across six countries (Germany, Spain, Estonia, Switzerland, United States, Singapore). Our Trust-Adoption Alignment Score (TAAS) measures five trust dimensions -- technical trust, interface trust, governance trust, ecosystem trust, and regulatory trust -- and correlates them with adoption outcomes. Regulatory trust emerges as the strongest predictor of enterprise adoption (beta = 0.42, p < 0.001), while interface trust is the strongest predictor of individual user adoption (beta = 0.38, p < 0.001). Technical trust -- the dimension most emphasised by the blockchain community -- ranks fourth for both user groups.